Answer:
13a² - 39a + 46
Step-by-step explanation:
To find g(a-2)+3g(2a), find each part using the function g(x)=x²-5x+8.
g(a-2) = (a-2)²-5(a-2)+8 = a² - 4a + 4-5a + 10+8 = a² - 9a + 22
3g(2a) = 3{(2a)²-5(2a)+8} = 3{ 4a² - 10a + 8} = 12a² - 30a + 24
Combine the values to find g(a-2)+3g(2a).
g(a-2)+3g(2a) = (a² - 9a + 22) + (12a² - 30a + 24) = 13a² - 39a + 46
Answer:
d = - 8
Step-by-step explanation:
3(d-8) - 5 = 9(d+2) + 1
3d-24 - 5 = 9d+18 + 1
3d - 29 = 9d + 19
9d - 3d = -29 - 19
6d = - 48
6d / 6 = -48/6
d = -8
62.5 is the answer to your question
Step-by-step explanation:
(x + y , x - y) = (4 , 2)
x+y=4 ------(1)
x-y=2 ------(2)
_____ (adding two equation)
2x=6
x=3
From equation 1
3+y=4
y=1